An original case of symmetric lipohypertrophy: case report and review of the literature - Nazareth Papazian; Joe Baroud; Saad Dibo; Elias Zgheib; Ghassan Abu-Sitta (Revista Brasileira de Cirurgia Plástica)
A middle-aged healthy woman who presented with longstanding history of slow growing masses located bilaterally and symmetrically on the upper and lower extremities closed to major joints. Imaging and pathology tests following excision of masses revealed normal subcutaneous fat. There was no evidence of well-circumscribed lipomas. A review of the literature identified a number of lipohypertrophic disorders, which may be present in a symmetrical fashion. The characteristics of the disorders, however, did not fully agree with characteristics observed in our patient. Although not absolute, the closest disease found to fit our case is a rare symmetrical lipodystrophy known as Madelung's disease. Of 150 reported cases, only 3 described involvement of lower extremities as seen in our case. We report a detailed description of a case, its management and post-operative follow-up. Different types of symmetrical lipodytrophies are also discussed.